EFEKTIVITAS CHEMICAL WEAPONS CONVINTION (CWC) DALAM PENGGUNAAN SENJATA KIMIA PADA KONFLIK DI SURIAH - Nazaria, Hilda Nazaria; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The study aims to analyze the effectiveness of the Chemical Weapons Convention (CWC) in tackling the use of chemical weapons by the Syrian Arab Republic regime during the period 2017-2023. Although Syria joined the CWC in 2013 and destroyed most of its chemical weapons supplies under the supervision of the Organization for the Prohibition of Chemical Weapons (OPCW), incidents of chemical use continued to be. The research uses qualitative methods with document analysis, OPCW reports, UN documents, journal articles, and news reports as primary data sources. The CWC's effectiveness in preventing the use of chemical weapons in Syria remains limited, and more coordinated international efforts as well as increased investigation and law enforcement capacity are essential. This research uses a qualitative method, with data collection techniques through literature studies sourced from several books, journals, articles, websites. This research uses the perspective of Constructivism, the theory of International Regime Effectiveness and the Level of System Analysis. The results of this paper identify that the effectiveness of the CWC has achieved many successes since its implementationDespite the challenges, especially in the context of Syria's compliance in implementing the CWC in Syria. The CWC remains an important instrument in the global effort to eliminate Chemical Weapons and prevent their future use. Keywords: Chemical Weapons Convention, Syria, Effectiveness, OPCW.